(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
Social network is term used to refer to the social structure that is made up of a set of social actors. The social actors in this case include organizations or individuals. Social networks allow people to interact and socialize as they get to learn and know each other. Through social networking sites, people from different parts of a country or the world also get to meet and interact. However, there have been issues with regards to social network privacy for those who use the internet to use social network sites. This paper will look at some of the factors that affect trust of the users as well as the privacy issues related to social networks (Fernandez, 2009).